Acquired resistance to EGFR targeted therapy in non-small cell lung cancer: Mechanisms and therapeutic strategies. (April 2018) - Lim, Sun Min; Syn, Nicholas L.; Cho, Byoung Chul; Soo, Ross A.
Highlights: Acquired resistance to EGFR targeted therapy can be EGFR-dependent or independent. Third-generation EGFR TKIs are in various stages of clinical development. Plasma detection of T790M resistance mutation enables serial monitoring. Integration of immune checkpoint inhibitors in EGFR-mutant patients is controversial. Abstract: The tyrosine kinase inhibitors (TKIs) directed at sensitizing mutations in the epidermal growth factor receptor (EGFR) gene represents a critical pillar in non-small cell lung cancer treatment. Despite the excellent disease control with initial EGFR TKI therapy, acquired resistance is ubiquitous and remains a key challenge. Investigations into the mechanisms which foster resistance to EGFR TKIs has led to the discovery of novel biomarkers and drug targets, and in turn has enabled the development of third-generation TKIs and proposals for rational therapeutic combinations. The threonine-to-methionine substitution mutation at position 790 (T790M) is clinically validated to engender refractoriness to first- and second-generation TKIs, and is a standard-of-care predictive biomarker used in therapeutic stratification. Clinical use of liquid biopsy approaches for assessment of T790M mutations continues to increase, with growing advocacy for serial monitoring of tumor evolution. For patients who are T790M-negative, cytotoxic chemotherapy or protracted EGFR TKI treatment are acceptable treatment standards after disease progression, although combinations of targeted therapies and checkpoint blockade immunotherapy may offer promising alternatives in the future. Among T790M-positive patients, the third-generation EGFR TKI, osimertinib, has shown superiority over both platinum-doublet chemotherapy and 1st generation EGFR TKI in randomized clinical trials, and exhibits enhanced in vitro selectivity for mutant EGFR receptors and pharmacokinetics compared to earlier-generation TKIs. This article appraises the key literature on the contemporary management of non-small cell lung cancer patients with acquired resistance to EGFR TKIs, and envisions future directions in translational and clinical research.